Comparison of Outcomes of Millard's Rotational Advancement Flap and Fisher's Techniques for Surgical Correction of UCLD - Syed Asif Hussain Shah, Muhammad Tauqeer Aslam, Muhammad Saad Zulfiqar, Tahir Mehmood, Muhammad Tahir Mehmood, Mushtaq Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of our study is to compare the surgical outcomes of two surgical techniques namely Fisher’s technique and Millard’s Rotational Advancement Flap, particularly in terms of white roll symmetry, lip length, lip height, scar quality, notching, cupids bow and alar base symmetry. Study design: Prospective Randomized Clinical Trial study. Place and duration of study: Department of Pediatric surgery, Sheikh Zayed Hospital, Rahim Yar Khan for a period of six months from 1st March 2021 to 31st August 2021. Patients and method: A total of 56 patients were enrolled in the study, equally divided into two groups. Group 1 will include patients undergoing treatment via Millard's Rotational Advancement Flap technique, while group 2 will include those receiving Fisher's procedure. A single consultant performed the procedure. Variables like lip length, Alar base symmetry, scar quality, cupids bow symmetry, and notching were accessed postoperative via the Steffensen grading method, and Vernier caliper was used for anthropometric measurements. The SPSS v 23 was used to evaluate the data. All numerical data were provided in mean and standard deviation (SD) formats. Frequencies were computed for qualitative data. Nonparametric tests (paired and unpaired t-tests) and parametric tests (Fisher's exact test) were utilized to compare the variables. P-value of < 0.05 was considered statistical significant. Results: Both groups had identical outcomes in terms of lip length, nasal symmetry, and alar dome. On the other hand, Fisher's approach was superior in terms of vermilion roll symmetry, white roll symmetry, scar appearance, and Cupid Bow. Anthropometric measures, such as lip height and breadth, were taken; however, the results were statistically insignificant. There was no discernible difference between the outcomes of complete and incomplete cleft lip. Conclusion: We propose using the Fisher's surgical method in unilateral cleft lip repair since it produces better outcomes than the Millard's procedure.